Implementasi dan Analisis Kinerja PJU Tenaga Surya untuk Peningkatan Kualitas Pencahayaan di Kawasan Technopark UPN “Veteran” Jawa Timur - Sumaidi; Wahyu Kartini; Anna Rumintang Nauli (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2026)
Poor lighting at the Technopark access of UPN "Veteran" Jawa Timur creates security risks and energy inefficiency. This study aims to implement an energy-independent Solar Street Light (PJU-TS) system to support the Green Campus vision. Using applied research methods, the activities included needs analysis, system design, physical installation of four All-in-One PJU-TS units, and performance evaluation. Post-installation results showed a drastic increase in average light intensity from <1 Lux to >10 Lux, meeting SNI 7391:2008 standards. The light sensor-based automatic control system proved effective in managing dusk-to-dawn operations, optimizing LiFePO4 battery usage. This implementation successfully eliminated blind spots, significantly improved the academic community's sense of security, and serves as a model for eco-friendly and energy-efficient campus infrastructure.